Autocracy login: internet censorship and civil society in the digital age. Issue 5 (3rd July 2020) - Chang, Chun-Chih; Lin, Thung-Hong
ABSTRACT: This study discusses whether the internet contributes to the rise of civil society or provides the state with a means to suppress civil society. By examining cross-sectional time-series data of 153 countries from 1995 to 2018, this study demonstrates that internet censorship is a reactive strategy used by autocracies to suppress civil society. Although rapid internet diffusion might undermine internet censorship in autocracies, since the Arab Spring, the use of censorship as a political reaction to technological diffusion and contentious politics worldwide has damaged the development of civil society. The autocratic reactive approach contributes to our understanding of information and communication technology, civil society, and authoritarianism. A more nuanced illustration of internet politics delivers a warning of technological threats to civil society.